Drivers' estimation of their travelling speed: a study on an expressway and a local road. Issue 3 (3rd July 2019) - Hussain, Qinaat; Alhajyaseen, Wael K. M.; Brijs, Kris; Pirdavani, Ali; Reinolsmann, Nora; Brijs, Tom
Abstract: Correctly estimating the travelling speed is essential for safety on the roads to ensure safer interactions with other drivers and to avoid violations of traffic regulations. Therefore, it is important to create understanding of the pattern of speed perception of drivers and the influencing factors. This study invited 40 drivers to participate in a field experiment measuring speed perception. The experiment was conducted using a test car equipped with high fidelity Global Positioning System (GPS). Data were collected for two settings (hidden versus revealed speedometer) and four requested speeds (50, 70, 80 and 100 km/h). An analysis of variance test was conducted along with separate t -tests and cumulative distributions for each speed independently. The results clearly show that there were significant differences in perceived speed between a hidden and revealed speedometer, between the first and second trial and among all the requested speeds. Participants drove significantly faster for all the requested speeds in the hidden speedometer setting. This shows that participants underestimated their speed. In case of complex situations, drivers may not be able to rely on speedometers and may cause a violation of law, unintentionally. Therefore, it is recommended to jurisdictions to consider these results while making decisions regarding speed management.